Ang Dumaracol ng Kalamianen Tagbanua ng hilagang Palawan isang panimulang paglalahad - Guieb, Eulalio R., III (2014)
This study is the first documentation of the long narrative song dumaracol of the Kalamianen Tagbanua of Northern Palawan on the islands bordering the towns of Taytay, El Nido, and Linapacan. The essay is the first in a multi-stage research that collects, records, documents, transcribes, translates into Filipino, and examines the said genre.

In the song, Dumaracol is the name of the hero of the Kalamianen Tagbanua. The song narrates the life, love, and struggles of Dumaracol in establishing and maintaining their community against the slave-raiding Moro. The essay discusses the different versions of the song, but highlights that by Blas Juan, one of the contemporary leaders of the Kalamianen Tagbanua of Pical Island in Linapacan. The essay also presents the processes of the research documentation of the song. It identifies and brings to the fore various issues in the preliminary understanding of dumaracol.
Keywords: Kalamianen Tagbanua (Palawan); Folk songs -- Palawan